Twist-tunable in-plane anisotropic polaritonic crystals - Capote-Robayna Nathaniel; Tresguerres-Mata Ana I. F.; Tarazaga Martín-Luengo Aitana; Terán-García Enrique; Martin-Moreno Luis; Alonso-González Pablo; Nikitin Alexey Y. (Nanophotonics)
van der Waals (vdW) materials supporting phonon polaritons (PhPs) – light coupled to lattice vibrations – have gathered significant interest because of their intrinsic anisotropy and low losses. In particular, α-MoO3 supports PhPs with in-plane anisotropic propagation, which has been exploited to tune the optical response of twisted bilayers and trilayers. Additionally, various studies have explored the realization of polaritonic crystals (PCs) – lattices with periods comparable to the polariton wavelength. PCs consisting of hole arrays etched in α-MoO3 slabs exhibit Bragg resonances dependent on the angle between the crystallographic axes and the lattice vectors. However, such PC concept, with a fixed orientation and size of its geometrical parameters, constrains practical applications and introduces additional scattering losses due to invasive fabrication processes. Here, we demonstrate a novel PC concept that overcomes these limitations, enabling low-loss optical tuning. It comprises a rotatable pristine α-MoO3 layer located on a periodic hole array fabricated in a metallic layer. Our design prevents degradation of the α-MoO3 optical properties caused by fabrication, preserving its intrinsic low-loss and in-plane anisotropic propagation of PhPs. The resulting PC exhibits rotation of the Bloch modes, which is experimentally visualized by scanning near-field microscopy. In addition, we experimentally determine the polaritons momentum and reconstruct their band structure. These results pave the way for mechanically tunable nano-optical components based on polaritons for potential lasing, sensing, or energy harvesting applications.